2013
DOI: 10.1038/nn.3479
|View full text |Cite
|
Sign up to set email alerts
|

Top3β is an RNA topoisomerase that works with fragile X syndrome protein to promote synapse formation

Abstract: Topoisomerases are crucial to solve DNA topological problems, but they have not been linked to RNA metabolism. Here we show that human topoisomerase 3β (Top3β) is an RNA topoisomerase that biochemically and genetically interacts with FMRP, a protein deficient in Fragile X syndrome and known to regulate translation of mRNAs important for neuronal function and autism. Notably, the FMRP-Top3β interaction is abolished by a disease-associated FMRP mutation, suggesting that Top3β may contribute to pathogenesis of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
317
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(341 citation statements)
references
References 62 publications
22
317
2
Order By: Relevance
“…In closing, it is relevant to note that in type IA topoisomerases, the Top3 enzymes also form 5Ј-tyrosyl catalytic intermediates (2,42). Thus, further studies are warranted to determine the potential relevance of TDP2 for the repair of Top3␣⅐DNA and Top3␤⅐DNA or RNA complexes (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…In closing, it is relevant to note that in type IA topoisomerases, the Top3 enzymes also form 5Ј-tyrosyl catalytic intermediates (2,42). Thus, further studies are warranted to determine the potential relevance of TDP2 for the repair of Top3␣⅐DNA and Top3␤⅐DNA or RNA complexes (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…The interest is further boosted by recent experiments demonstrating that human and Drosophila topoisomerase 3β (Top3β) is associated with mRNA in cytoplasm and has RNA topoisomerase activity (11,12). The deficiency in this enzyme is attributed to one of the causative mutations for schizophrenia and cognitive disorder (11, 12) and results in abnormal synaptic structures in Drosophila (12).…”
mentioning
confidence: 99%
“…FMRP is preferentially localized in the coding regions of mRNA and plays a role in inhibiting the translation of mRNA relevant to synaptic functions in neuronal cells (17). It is thus suggested that Top3β may also have a role in translation through its RNA topoisomerase activity in modulating the complex structures of folded mRNA (12). Whereas Top3β can have important functions in two processes of gene expression in nucleus and cytoplasm through its interactions with TDRD3, it is unclear whether TDRD3 has any additional role in regulating Top3β activity, beyond its targeting function of directing Top3β to critical sites in subcellular compartments.…”
mentioning
confidence: 99%
“…For instance, topoisomerase 1 (TOP1) and topoisomerase 2 (TOP2) inhibitors transcriptionally up-regulate the paternal copy of Ubiquitin-protein ligase E3A (Ube3a) (5), a gene that affects synaptic activity and that is deleted or duplicated in distinct neurodevelopmental disorders (Angelman syndrome and autism, respectively) (6,7). Moreover, a de novo mutation in Top1 and de novo mutations in genes that interact with Top1 and Top3b were identified recently in patients with autism (8,9), whereas deletion of Top3b increases the risk for schizophrenia and intellectual disability (10,11). Top2b is also required for axon outgrowth in different regions of the nervous system and for the survival of postmitotic neurons (12)(13)(14)(15).…”
mentioning
confidence: 99%